TINGKAT KEPUASAN MAHASISWA PADA PEMBELAJARAN JARAK JAUH MATA KULIAH HYOUKI - Lev Zeikov; Nana Rahayu; Charlina Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The level of student satisfaction is a student's positive attitude towards educational services in higher education because there is a match between the expectations of the service compared to the reality it receives. This study discusses how the level of student satisfaction in distance learning in the Hyouki course. The purpose of this study was to explain the level of student satisfaction in distance learning for the Hyouki course. The method used in this research is descriptive quantitative. quantitative descriptive is a type of research used to analyze data by describing or describing the data that has been collected as it is. The results showed that the level of student satisfaction in distance learning for the Hyouki course was good/satisfied.Key Words: The Level of Student Satisfaction, Distance Learning, Hyouki